On the Statistical Convergence of Order ? in Paranormed Space - Ercan, Sinan (Mdpi, 2018)
The aim of the present work is to introduce notions of statistical convergence, strongly p-Cesaro summability and the statistically Cauchy sequence of order alpha in paranormed spaces. Some certain topological properties of these new concepts are examined. Furthermore, we introduce the some inclusion relations among them.
Keywords: sequences; statistical convergence; Cesaro summability; paranormed space